Archaeology of Maldives and Lakshadweep - Sharma,A.K (B.R, 2019)
The book gives on the spot account of the archaeological finds that were located and exposed in various islands of Maldives and Lakshadweep. It Shows the richness of the islands, particularly during Buddhist era when Sanghmitra is supposed to have visited them. It stresses the need to expose and preserve the remains of glorious bygone days